CAN THE WELFARE OF HINDU CLERGY IN BALI BE ASSESSED USING AMARTYA SEN'S CAPABILITY APPROACH: DAPATKAH KESEJAHTERAAN ROHANIAWAN HINDU DI BALI DIKAJI DENGAN PENDEKATAN KAPABILITAS AMARTYA SEN - Anak Agung Ketut Ayuningsasi; Made Kembar Sri Budhi; I Nyoman Mahaendra Yasa; A.A.I.N. Marhaeni; I Ketut Sudibia; Made Heny Urmila Dewi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The movement space of Sulinggih, the Balinese Hindu clergy, is severely restricted in various aspects due to the rules set by the Balinese community to preserve its sanctity. These social rules dictate that Sulinggih must relinquish secular work and focus solely on religious activities. This study aims to explore the applicability of Amartya Sen's Capability Approach theory in analyzing the well-being of Hindu clergy in Bali. The research employs a qualitative method, specifically a literature study. The study reviews the variables identified by Amartya Sen in his writings and studies, which have also been further examined by economists. Based on the analysis, this study proposes a conceptual framework to elucidate and predict how the variables in Sen's theory influence the welfare outcomes of Hindu clergy in Bali. The framework considers commodities and capabilities as potential mediating variables, while conversion factors and social choices are seen as factors that moderate the impact of resources on the attainment of functionings.